2016
DOI: 10.1073/pnas.1524907113
|View full text |Cite
|
Sign up to set email alerts
|

Pubertal activation of estrogen receptor α in the medial amygdala is essential for the full expression of male social behavior in mice

Abstract: Testosterone plays a central role in the facilitation of male-type social behaviors, such as sexual and aggressive behaviors, and the development of their neural bases in male mice. The action of testosterone via estrogen receptor (ER) α, after being aromatized to estradiol, has been suggested to be crucial for the full expression of these behaviors. We previously reported that silencing of ERα in adult male mice with the use of a virally mediated RNAi method in the medial preoptic area (MPOA) greatly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Of these, the POA and BnST have larger roles in social preference, mating and territorial aggression, while the MePD is linked to social recognition (Ervin et al, 2015, Russell et al, 2012, Sano et al, 2013). Other studies have linked the MePD with aggressive behaviors (Sano et al, 2016, Unger et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Of these, the POA and BnST have larger roles in social preference, mating and territorial aggression, while the MePD is linked to social recognition (Ervin et al, 2015, Russell et al, 2012, Sano et al, 2013). Other studies have linked the MePD with aggressive behaviors (Sano et al, 2016, Unger et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…For single immunostaining for ERα or AR, brain sections were washed and incubated with rabbit anti-ERα (1:5000, C1355, Millipore) or anti-AR (1:500, sc-816, Santa Cruz biotechnology) antibodies, of which the specificities were verified using gene-deficient mice, shRNA-based gene knockdown or preabsorption with antigen 12 , 13 , 55 , 56 . The sections were washed and immersed in Alexa568-conjugated donkey anti-rabbit IgG antibody (1:250, A10037, Thermo scientific) and Hoechst 33342 (1 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…So far, these studies manipulated site-specific activation of ER by 17β-E only in adulthood. A recent study has reported that site-specific manipulation of ERα expression in sexually immature male mice has different effects (Sano et al, 2016) than in adult mice. Pre-pubertal (21days old) silencing of ERα in the MeA significantly reduces both sexual and aggressive behavior in adulthood.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, it is concluded that ER activation in the MeA during pubertal period is crucial for male mice to fully express their male-type social behaviors in adulthood. Furthermore, pre-pubertal knockdown of ERα in male mice reduces the number of neurons in the MeA to the levels of female mice (Sano et al, 2016). It is expected that future studies will elucidate the exact mechanisms of ERα action that results in full masculinization of neural networks for male-type social behavior, during the pubertal period.…”
Section: Accepted Manuscriptmentioning
confidence: 99%